Pleistocene marine terraces of the Wellington south coast – their distribution across multiple active faults at the southern Hikurangi subduction margin, Aotearoa New Zealand. Issue 1 (2nd January 2022) - Ninis, Dee; Little, Timothy; Litchfield, Nicola; Wang, Ningsheng; Jacobs, Katrina; Henderson, C. Mark
ABSTRACT: Along the south coast of the North Island of New Zealand, elevated Pleistocene marine terraces provide evidence for vertical deformation associated with active crustal faults and the westward subduction of the Pacific Plate at the southern Hikurangi margin. We have reassessed the age and elevation of these terraces. Optically Stimulated Luminescence (OSL) data of their cover bed sediments (20 new ages) provide the first numerical ages for most of these terraces. Shore platform elevations have been surveyed using differential Global Navigation Satellite System (GNSS) measurements of the wave-cut bedrock straths underlying these terraces. These new data allow the terraces to be temporally correlated across the margin. Seven different-aged terraces were identified and mapped along the Wellington south coast; these are preserved discontinuously between the westernmost site at Tongue Point, and Ngawi near Cape Palliser, to the east. The OSL data indicate that most of these terraces formed at MIS 5a, 5c, 5e (Last Interglacial) and 7a. The terraces are best preserved within the Hikurangi margin forearc, where they decrease in altitude towards the west, indicating long wavelength, westward tectonic tilting. The terraces are locally offset by a number of active crustal faults, most notably the Wairarapa and Ohariu faults.